Exploring opportunities in Africa’s dairy production: digital transition as a catalyst for marketing innovation and value chain synergies – a systematic review laying foundations for future research - Vuvor, Courage Maccarthy; Epifani, Stefano; Pulina, Giuseppe (Frontiers in Animal Science, 2025)
This systematic review examines the role of digital technologies in enhancing marketing and value chain integration in Africa’s dairy sector. Drawing on 14 peer-reviewed studies conducted between 2014 and 2025, the review explores the types of digital tools being adopted, assesses their impact on dairy market dynamics and supply chain coordination, and identifies the structural, economic, and socio-cultural barriers that hinder their broader adoption. The findings reveal that mobile technologies, particularly SMS-based services and applications remain the most widely utilized, offering farmers access to market prices, buyer networks, and advisory services. More advanced tools are being introduced gradually and show promise in improving traceability, milk quality monitoring, resource optimization, and transparency across the value chain. Despite these advances, significant challenges persist. The review identifies limited internet connectivity, high costs of digital devices and services, low levels of digital literacy, and gender disparities as major obstacles, particularly in rural areas. These challenges are exacerbated by inadequate infrastructure and a lack of targeted training and support mechanisms. The review concludes that while digital technologies offer transformative potential for improving efficiency, profitability, and equity in the dairy sector, their success depends on context-specific strategies, inclusive design, and strong multi-stakeholder collaboration. It calls for future research to address regional gaps, particularly in North and Central Africa, and to focus on the long-term sustainability and social dimensions of digital transformation. By addressing these gaps and fostering enabling environments, digital innovation can serve as a catalyst for a more inclusive, productive, and resilient dairy industry across the African continent.